ONTOLOGI SOSIAL: BAGAIMANA MASYARAKAT MENCIPTAKAN REALITAS - Adisty Ningtiyas; Munir; Ismail Sukardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Social ontology is the philosophical study of the nature of social entities formed through collective interactions and agreements in society, as proposed by Peter L. Berger and Thomas Luckmann in The Social Construction of Reality (1966). This article analyzes the dialectical process of reality construction—externalization (the projection of human ideas onto the outside world), objectivation (social structures becoming “objective”), and internalization (individuals adopting them as reality)—as well as John Searle’s contributions on status functions such as money and institutions. Through empirical examples (fiat money, gender norms, the state as an imagined community), ethical implications (power shaping reality), and contemporary relevance (social media, the AI ​​metaverse), the article highlights the fragility of social reality that relies on collective intentionality. A critique of relativism and recommendations for critical deconstruction are offered for the digital age of 2026. Keywords: social ontology, reality construction, Berger-Luckmann, Searle, intersubjectivity.